Acyl-CoA-Binding Protein ACBP1 Modulates Sterol Synthesis during Embryogenesis . Issue 3 (12th May 2017) - Lung, Shiu-Cheung; Liao, Pan; Yeung, Edward C.; Hsiao, An-Shan; Xue, Yan; Chye, Mee-Len
Abstract : Arabidopsis acyl-CoA-binding protein ACBP1 forms an endoplasmic reticulum-associated complex with STEROL C4-METHYL OXIDASE1-1 and negatively modulates sterol synthesis during embryogenesis. Abstract: Fatty acids (FA s) and sterols are primary metabolites that exert interrelated functions as structural and signaling lipids. Despite their common syntheses from acetyl-coenzyme A, homeostatic cross talk remains enigmatic. Six Arabidopsis ( Arabidopsis thaliana ) acyl-coenzyme A-binding proteins (ACBPs) are involved in FA metabolism. ACBP1 interacts with PHOSPHOLIPASE Dα1 and regulates phospholipid composition. Here, its specific role in the negative modulation of sterol synthesis during embryogenesis is reported. ACBP1, likely in a liganded state, interacts with STEROL C4-METHYL OXIDASE1-1 (SMO1-1), a rate-limiting enzyme in the sterol pathway. Proembryo abortion in the double mutant indicated that the ACBP1-SMO1-1 interaction is synthetic lethal, corroborating with their strong promoter activities in developing ovules. Gas chromatography-mass spectrometry revealed quantitative and compositional changes in FA s and sterols upon overexpression or mutation of ACBP1 and/or SMO1-1 . Aberrant levels of these metabolites may account for the downstream defect in lipid signaling. GLABRA2 ( GL2 ), encoding a phospholipid/sterol-binding homeodomain transcription factor, was up-regulated in developing seeds of acbp1, smo1-1, and ACBP1 +/− smo1-1 in comparison with the wild type. Consistent with the corresponding transcriptional alteration of GL2 targets, high-oil, low-mucilage phenotypes of gl2 were phenocopied in ACBP1 +/− smo1-1 . Thus, ACBP1 appears to modulate the metabolism of two important lipid classes (FA s and sterols) influencing cellular signaling.